Combined mineralocorticoid and glucocorticoid deficiency is caused by a novel founder nicotinamide nucleotide transhydrogenase mutation that alters mitochondrial morphology and increases oxidative stress. Issue 9 (12th June 2015) - Weinberg-Shukron, Ariella; Abu-Libdeh, Abdulsalam; Zhadeh, Fouad; Carmel, Liran; Kogot-Levin, Aviram; Kamal, Lara; Kanaan, Moien; Zeligson, Sharon; Renbaum, Paul; Levy-Lahad, Ephrat; Zangen, David
Abstract : Background: Familial glucocorticoid deficiency (FGD) reflects specific failure of adrenocortical glucocorticoid production in response to adrenocorticotropic hormone (ACTH). Most cases are caused by mutations encoding ACTH-receptor components ( MC2R, MRAP ) or the general steroidogenesis protein (StAR). Recently, nicotinamide nucleotide transhydrogenase ( NNT ) mutations were found to cause FGD through a postulated mechanism resulting from decreased detoxification of reactive oxygen species (ROS) in adrenocortical cells. Methods and results: In a consanguineous Palestinian family with combined mineralocorticoid and glucocorticoid deficiency, whole-exome sequencing revealed a novel homozygous NNT _c.598 G>A, p.G200S, mutation. Another affected, unrelated Palestinian child was also homozygous for NNT_p.G200S. Haplotype analysis showed this mutation is ancestral; carrier frequency in ethnically matched controls is 1/200. Assessment of patient fibroblasts for ROS production, ATP content and mitochondrial morphology showed that biallelic NNT mutations result in increased levels of ROS, lower ATP content and morphological mitochondrial defects. Conclusions: This report of a novel NNT mutation, p.G200S, expands the phenotype of NNT mutations to include mineralocorticoid deficiency. We provide the first patient-based evidence that NNT mutations can cause oxidative stress and both phenotypic and functional mitochondrial defects. These results directly demonstrate the importance of NNT to mitochondrial function in the setting of adrenocortical insufficiency.